Risk factors of metabolic syndrome in women of reproductive age at mining area - Luthviatin, Novia; Setiani, Onny; Widjanarko, Bagoes; Rahfiludin, Mohammad Zen; Kartini, Apoina; Raharjo, Mursid (International Journal of Public Health Science (IJPHS), 2024)
Lead is one of the four most dangerous heavy metal pollutants, toxic to human health, and linked to metabolic syndrome (MetS). This research aimed to analyze the relationship between respondent characteristics, blood lead level (BLL), nutrition intake, and physical activity to MetS and its components in women of reproductive age at Pemali District Mining Area, Bangka Belitung Regency. This research was conducted with a case-control approach involving 70 women of reproductive age (35 cases and 35 controls). Data was analyzed using chi-square and Mann-Witney tests for bivariate analysis and regression test logistics for multivariate analysis. Based on bivariate analysis, there is a significant relationship between body mass index (BMI) (p=0.000), salt intake (p=0.017), and seasoning intake (p=0.017) to MetS; meanwhile, BLL is not associated with MetS (p=0.473) but are associated with high-density lipoprotein cholesterol (HDLC) (p=0.019). Multivariate test results show that BMI (p=0.000; OR=7.995) and salt intake (p=0.030; OR=6.812) are significant risk factors for MetS. Women of reproductive age must maintain BMI within normal levels and reduce daily salt intake to prevent the occurrence of MetS. BLL must be controlled to prevent decreased HDLC levels in women of reproductive age.